Development of nano-satellite inter-satellite communications - Loh, Kevin Han Yong. (2011)
This project is part of NTU’s nano-satellite development program, and deals with the simulation of inter-satellite communications between the nano-satellite and pico-satellite. The scope of the project is to study the communication link between two satellites orbiting in space, and implementing a tool to simulate the orbit and communication link between the two satellites.